Applying Text Mining Methods to Construct a Domain Ontology from Definitions - Margarida Ramos; Rute Costa (Umanistica Digitale)
This paper aims to describe a text-mining approach on a domain corpus (cork) within the theoretical framework of the dual dimension of terminology to create a terminological dictionary and correlate it with an ontology. We will make some considerations on (i) domain specificities; (ii) lexical markers; (iii) automatic corpus processing using Sketch Engine; (iv) representation of lexical networks using CmapTools; and (v) representation of the concept system using Protégé. The goal of the ontology is to logically support the coherence and quality of the natural language definitions contained in the terminological resource.